Assessment of different combinations of ammoniated halide salt for resorption cooling system with and without heat-recovery using sorption thermodynamic properties. (1st October 2020) - Sharma, Rakesh; Kumar, E. Anil
Highlights: Different combinations of halide salts for resorption cooling system. Estimation of operating parameters and performance of resorption cooling system using measured sorption properties. Analysis of heat-recovery resorption cooling system. Pairing of two different LTS with MTS and HTS in heat-recovery resorption cooling system. Abstract: This work deals with the thermodynamic study of a resorption cooling system with and without heat-recovery to classify the best combination of halide salts. As the ammonia sorption characteristics are far from the ideal case, like adsorption capacity varies with temperature and reaction enthalpy is distinct for adsorption and desorption, the novelty of this work is to perform an analysis using measured sorption thermodynamic properties of NaBr, NH4 Cl, KI, CaCl2, SrCl2, MnCl2, FeCl2 to precisely select the appropriate combination, operating parameters and size of reactor bed. The thermodynamic coefficient of performance ( COPth ) of the resorption cooling system decreases in the following order of refrigerating salt NH4 Cl > KI > NaBr and regenerating salt CaCl2 > SrCl2 > MnCl2 > FeCl2, according to their desorption enthalpies. The highest value of COPth of the resorption cooling system is 0.43 for the pair NH4 Cl–CaCl2 . Due to high desorption pressures of NaBr than NH4 Cl or KI, NaBr is suitable refrigerating salt at temperatures below 0 ℃. In a heat-recovery resorption cooling system, the pairs of NH4 Cl–MnCl2 and KI–MnCl2 are not possible because of the increase in adsorption pressure of MnCl2 at high temperatures, whereas the total heat released by MnCl2 is inadequate to desorb ammonia from SrCl2 to facilitate the heat-recovery process. However, two different low-temperature salts can be paired with each of the medium-temperature and high-temperature salts in the heat-recovery system. The thermodynamic coefficient of performance is attained as 0.64 for the combination NH4 Cl–CaCl2 : NaBr–MnCl2 .